2021
DOI: 10.3390/toxins13050338
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors of Local Tissue Necrosis after Taiwan Cobra Bites: A Secondary Analysis of the Clinical Significance of Venom Detection in Patients of Cobra Snakebites

Abstract: Local tissue swelling, inflammation, and wound necrosis are observed in Taiwan cobra bites. Knowledge of the factors influencing local tissue necrosis after cobra bites might improve the cobra bite treatment strategy. Therefore, we aimed to explore the factors influencing local tissue necrosis after cobra bites. This was a retrospective observational cohort study. All patients clinical presentations including serum venom levels for determining the influential factors in this study were obtained from Hung et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Therefore, cobra bites should immediately be cleaned, debrided, and dressed as soon as possible, and given antibiotics to reduce the incidence of infection [42,43]. Additionally, some reports have shown that wound necrosis is related to the patient's treatment time, the concentration of toxin, and the dose of anti-snake venom; the less toxin secreted by the cobra, the earlier the patient visits the medical practitioner, and the higher the dose of anti-snake venom used, the lower the probability of wound necrosis [44,45]. Pharmacokinetics indicated that higher doses of anti-snake venom administered for cobra envenoming facilitate the neutralization of venom antigens [46], but still can't completely neutralize the residual venom depot at the site of wound [47], which may remain active and slowly lead to local tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cobra bites should immediately be cleaned, debrided, and dressed as soon as possible, and given antibiotics to reduce the incidence of infection [42,43]. Additionally, some reports have shown that wound necrosis is related to the patient's treatment time, the concentration of toxin, and the dose of anti-snake venom; the less toxin secreted by the cobra, the earlier the patient visits the medical practitioner, and the higher the dose of anti-snake venom used, the lower the probability of wound necrosis [44,45]. Pharmacokinetics indicated that higher doses of anti-snake venom administered for cobra envenoming facilitate the neutralization of venom antigens [46], but still can't completely neutralize the residual venom depot at the site of wound [47], which may remain active and slowly lead to local tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Lin and Alcoba found only (29,6%) and (5%) of the sample that presented with cell necrotic. [22], [23] Most snake venom contains hydro lithic enzymes such as Metallo Proteinase, PLA2, and 3-Finger Toxin that are responsible for cell necrotic. These components cause the destruction of local tissue by inducing Neutrophil Extracellular Traps (NETs), that blockade the blood flow and fill the site of the bite with venom, which later on increases the cytotoxicity.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…The need to deliver antivenom intravenously by a medical professional in a clinical environment prolongs the time from bite to treatment by an average of five to nine hours due to poor hospital-accessibility in the remote, rural tropical regions where most snakebites occur ( 22, 25, 26 ). Furthermore, intravenous antivenom antibodies are too large (typically ∼110 or ∼150 kDa) to rapidly penetrate the envenomed peripheral tissue and neutralise the aetiological cytotoxins – rendering antivenom treatment largely ineffective in reversing the swelling, blistering and necrotic outcomes of local envenoming ( 1, 22, 23, 27, 28 ). Collectively, these limitations highlight why the development of effective therapeutics is one of the core goals of the WHO’s roadmap to reduce the impact of snakebite envenoming ( 2 ).…”
Section: Introductionmentioning
confidence: 99%